Subsidence and Induced Subsoil Cracking in the Southeastern of Mexico City - Silvia García; Joel Merlos; Paulina Trejo (Advances in Civil Engineering)
Cracking of soils associated with subsidence is a complex and multiparametric problem. Local soil conditions could be responsible for the dramatic differential settlements and fissures manifest when the water pumping reduces the volume of the compressible strata. This situation is of extreme importance due to the level of damage to urban infrastructure and buried facilities (gas, water, and drainage) as well as to housing structures. In this research, using a simple geotechnical model of subsidence (finite element method, Mohr–Coulomb criterion) parametric combinations of materials and basement geometry are tested to define the geotechnical settings more susceptible to deformation and derived cracking. These approximations are compared with measurements and field surveys in Mexico City to validate the hypothesis. Defining the zones that are more susceptible to respond with cracking due to the phenomenon of subsidence can be especially important when designing urban development programs, restoration campaigns for buried pipes, even for construction and operation of new pumping wells.